Chuck. The complete first season [videorecording (DVD)] - Schwartz, Josh, 1976-; Fedak, Chris; Marks, Paul; Levi, Zachary, 1980-; Strahovski, Yvonne, 1982-; Gomez, Joshua, 1975-; Lancaster, Sarah, 1980-; Baldwin, Adam, 1962-; McG (Joseph McGinty Nichol); McNeill, Robert Duncan, 1964-; Miller, Matthew (Television producer); Ensler, Jason, 1970-; et al. (Chuck (Television program), 2008)
Ever since Chuck Bartowski, ace computer geek, unwittingly downloaded stolen government secrets into his brain, action, excitement, and a cool secret-agent girlfriend have entered his life.